2017
DOI: 10.1590/0103-6513.223816
|View full text |Cite
|
Sign up to set email alerts
|

Application of Project-Based Learning in the first year of an Industrial Engineering Program: lessons learned and challenges

Abstract: The Industrial Engineering Program at the School of Engineering of Lorena at the University of São Paulo has been using the Project-Based Learning (PBL) methodology in the first term of the academic year since 2013. This article describes the experience of the first four years of the use, the lessons learned, and the remaining challenges. The use of PBL has been widely recognized by the students as one of the Industrial Engineering program's differentiating features. Lessons have been learned continuously and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 23 publications
(32 reference statements)
1
26
0
3
Order By: Relevance
“…Additionally, it is clear that, in the case of Engineering, active learning strategies involving collaborative team activities are the best for simulating the real situations faced by engineers in today's world (Graaff, Saunders-Smits & Nieweg, 2005). Thus, we highlight Project-Based Learning (Pereira, Barreto & Pazeti., 2017;Stozhko, Bortnik, Mironova, Tchernysheva & Podshivalova., 2015;Treadwell, 2018), Problem-Based Learning (Graaff & Kolmos, 2007;Yadav, Subedi, Lundeberg & Bunting, 2011), Team-Based Learning (Koles, Stolfi, Borges, Nelson & Parmelle, 2010;Parmelee, Michaelsen, Cook & Hudes, 2012;Zhang, Wu & Li, 2018), and Design Thinking (Glen, Suciu, Baughn & Anson, 2015; Design Thinking for educators, 2013; Ingle, 2013), among others.…”
Section: Active Learning Strategies and Their Relevance For The Todaymentioning
confidence: 99%
“…Additionally, it is clear that, in the case of Engineering, active learning strategies involving collaborative team activities are the best for simulating the real situations faced by engineers in today's world (Graaff, Saunders-Smits & Nieweg, 2005). Thus, we highlight Project-Based Learning (Pereira, Barreto & Pazeti., 2017;Stozhko, Bortnik, Mironova, Tchernysheva & Podshivalova., 2015;Treadwell, 2018), Problem-Based Learning (Graaff & Kolmos, 2007;Yadav, Subedi, Lundeberg & Bunting, 2011), Team-Based Learning (Koles, Stolfi, Borges, Nelson & Parmelle, 2010;Parmelee, Michaelsen, Cook & Hudes, 2012;Zhang, Wu & Li, 2018), and Design Thinking (Glen, Suciu, Baughn & Anson, 2015; Design Thinking for educators, 2013; Ingle, 2013), among others.…”
Section: Active Learning Strategies and Their Relevance For The Todaymentioning
confidence: 99%
“…In the PBL methodology students are arranged in teams which in turn receive a problem situation in which the concepts of the discipline are required to solve it. The problem situation is based on cases experienced by professionals working in the profession intended by students (Pereira et. al, 2017;Milss and Treagust 2003;Santos et.…”
Section: Problem Based Learningmentioning
confidence: 99%
“…Integration of STEM contents is not a streamline task and in Industrial Engineering programs is reportedly a challenging endeavour (Pereira et al, 2017), giving motivation for the research reported on this paper. The delivery of individual STEM subjects is the traditional way and although the benefits of interdisciplinary collaboration, the attempt at integration is not commonly applied (Bell, 2016).…”
Section: Integration Of Stem In Pbl Projectsmentioning
confidence: 99%